Development, Characterization, and Evaluation of Hepatoprotective effect of Abutilon indicum and Piper longum Phytosomes - Sharma S.; Sahu A. (My University, 2025)
Background: Evidences from ethnopharmacological practices have shown that combination of Abutilon indicum and Piper longum are traditionally used to treat symptoms of the liver disorder. The hypothesis is phytosomes of a combination of both crude drug extract will be more effective and safe as hepatoprotective agent. Aim: Present work is aimed at development and characterization of phytosomes containing ethanolic extract of both drugs to meet the need for better effectiveness and safety. Materials and Methods: Phytosomes were formulated by using Indena's patented process. Characterization involved following parameters: Particle size determination, percentage yield, entrapment efficiency, differential scanning calorimetry, scanning electron microscope, fourier transform infrared spectroscopy, and high performance thin liquid chromatography. Liver damage was induced in adult Charles foster rats (150 ± 10 g) with CCl 4 in olive oil (1:1 v/v, i.p) 1 ml/kg once daily for 7 days. LIV 52 (1 ml/kg per oral [p.o]), ethanolic extract of A. indicum and P. longum combination (100, 200, and 400 mg/kg p.o) and phytosomes (100 mg/kg p.o.) was given 3 days prior to CCl 4 administration. Estimation of liver marker enzymes and histopathological studies were done. Result was analyzed by using (analysis of variance) followed by Student-Newman-Keuls test. Result: Combined extract has shown hepatoprotective activity but phytosomal formulation has more potent hepatoprotective effect on CCl 4 induced liver toxicity at very low dose comparative to a higher dose of combined extract. Conclusion: Novel approach for herbal drug delivery is more prominent than conventional which improves bioavailability of polar extract and also patient compliance.